PACAP Inhibits β-cell Mass Expansion in a Mouse Model of Type II Diabetes: Persistent Suppressive Effects on Islet Density - Inoue, Hiroaki; Shintani, Norihito; Sakurai, Yusuke; Higashi, Shintaro; Hayata-Takano, Atsuko; Baba, Akemichi; Hashimoto, Hitoshi (Frontiers in Endocrinology, 2013)
Pituitary adenylate cyclase-activating polypeptide (PACAP) is a potent insulinotropic G-protein-coupled receptor ligand, for which morphoregulative roles in pancreatic islets have recently been suggested. Here, we evaluated the effects of pancreatic overexpression of PACAP on morphometric changes of islets in a severe type II diabetes model. Following cross-breeding of obese-diabetic model KKAy mice with mice overexpressing PACAP in their pancreatic β-cells, the resulting KKAy mice with or without PACAP transgene (PACAP/+:Ay/+ or Ay/+ mice) were fed with a high-fat diet up to the age of 11 months. Pancreatic sections from 5 and 11 month old littermates were examined. Histomorphometric analyses revealed significant suppression of islet mass expansion in PACAP/+:Ay/+ mice compared with Ay/+ mice at 11 months, but no significant difference between PACAP/+ and +/+ (wild-type) mice, as previously reported. The suppressed islet mass in PACAP/+:Ay/+ mice was due to a decrease in islet density but not islet size. In addition, the density of tiny islets (<0.001 mm2) and of insulin-positive clusters in ductal structures were markedly decreased in PACAP/+:Ay/+ mice compared with Ay/+ mice at 5 months of age. In contrast, PACAP overexpression caused no significant effects on the level of aldehyde-fuchsin reagent staining (a measure of β-cell granulation) or the volume and localization of glucagon-positive cells in the pancreas. These results support previously reported inhibitory effects of PACAP on pancreatic islet mass expansion, and suggest it has persistent suppressive effects on pancreatic islet density which may be related with ductal cell-associated islet neogenesis in type II diabetes.